HOW PRICE PERCEPTION AND TRUST AFFECTED MILLENIAL ONLINE BUYING INTEREST DURING COVID-19 PANDEMIC IN WEST JAVA - Harrie Lutfie; Dandy Marcelino (Dinasti Publisher, 2020)
The implementation of Work From Home also has an impact on the trend of buying interest online. The trend of buying interest online is usually carried out by young consumers or can be called as millenials because they are the ones who use online facilities to fulfill their needs even though they are not in a Covid-19 condition. Interest in buying online is influenced by price perception and level of consumer trust. Aim of this research for find out the influence of price perceptions and consumer trust on online buying interest during the Covid-19 pandemic in millennial consumers in West Java. From the results of this study, it can be concluded that millennial consumers' online purchase interest during the COVID-19 outbreak was influenced by product price perceptions and millennial consumer confidence. These results indicate that efforts to increase interest in buying online can be done by first increasing millennial consumer confidence.